Geothermal energy as a source of electricity. A worldwide survey of the design and operation of geothermal power plants - DiPippo, R. (Southeastern Massachusetts Univ., North Dartmouth (USA), 1980)
An overview of geothermal power generation is presented. A survey of geothermal power plants is given for the following countries: China, El Salvador, Iceland, Italy, Japan, Mexico, New Zealand, Philippines, Turkey, USSR, and USA. A survey of countries planning geothermal power plants is included. (MHR)